(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to provide a theoretical framework explaining the impact of cloud computing and its fields on information technology, as cloud computing has achieved a significant change in the economics and sustainability of information technology, which is one of the most innovative technological models for the development and exploitation of infrastructure resources in the world, especially at the level of informatics. The shift from purchasing infrastructure and technology applications as an acquired product to a well-delivered service. The user no longer needs to search for large funding to purchase infrastructure equipment and related applications and a license to operate them. The cloud computing profession has not been isolated from keeping pace with these technological developments, as those in charge and practitioners should understand these changes that require reorganizing the work of the units they serve, as it should Programmers should be aware of the need to analyze and evaluate impacts and changes to information technology.